A new species of the genus Ceratagallia (Cicadellidae: Megophthalminae) from Central Mexico - Pinedo-Escatel, J. A.; Dietrich, C. H. (Zootaxa, 2017)
Ceratagallia (Ceratagallia) brailovskyi sp. nov., is here described and illustrated from Central Mexico. The new species appears to be closely related to the C. bigeloviae species group, which includes previously described Mexican species. A key, species list, and distributional map for Ceratagallia in Mexico are provided.